Accommodating Learners’ Multilingual Capabilities in an English First Additional Language Classroom - Kufakunesu Zano (Journal of Languages and Language Teaching, 2022)
Debatably, in South Africa, there is an absence of a consensus about a teaching method that can inform multilanguage usage for English first additional language learners in the Further Education and Training phase. This study argues that translanguaging can be the latest all-embracing approach in language policy and assessment needed to substitute previous linguistic practices that treated languages as separate entities in a globalised world. The study aims to determine how group work promotes learners’ different multilingual capabilities among learners in an English first additional language context in the Further Education and Training phase. It took place in a multilingual Grade 11 classroom. For this qualitative study, only 24 Grade 11 learners were used as participants in 4 focus groups for data collection. The results indicate that engaging in group work increases the time  English first additional language learners spend actively using their home languages with their peers. Learning English within mixed linguistic groups, learners often draw on their existing languages to learn and to communicate with their teachers and peers. Therefore, distinguishing language upbringings as a reserve might produce positive results in the classroom when teaching English to English first additional language learners as learners showcase their identities in collaboration with their contemporaries. Group work creates a space where translanguaging can easily take place and it is a good exemplification of the power processes that underlie the classroom as learning becomes learner-centric. It was concluded that group work can serve as an enabler for translanguaging, harnessing learners’ different multilingual capabilities for a better understanding of their work.